Pengaruh Perceived Value Terhadap Revisit Intention Di Daya Tarik Wisata Linggai Park Maninjau Kabupeten Agam - Riri Anggraini; Nidia Wulansari (Lembaga Pengembangan Kinerja Dosen, 2024)
This research motivation is the decrease in revisit intention at Linggai Park Maninjau tourism attraction, which is evidenced by visitor complaints expressed with social media. The research purposess is to reveal the perceived value influence on revisit intention at Linggai Park Maninjau tourism attraction in Agam Regency. The method for research used included approach quantitative with a causal associative. The population consists of visitors who visit Linggai Park Maninjau, and the average visitors number from July to December 2022 is 3,095 visitors. Therefore, a sample of 226 respondents was determined. Data was collected from a questionnaire where validity and reliability has been tested. Simple linear regression and coefficient of determination were used to test the research hypothesis with the assistance of SPSS version 25.00. The results obtained a value of F at 586.521 with a level of significance is 0.000 < 0.05, indicated that accept for Ha and reject for H0, and there is a significant influence from perceived score and revisit intention. Furthermore, the coefficient of regression perceived value is 0.828 with a significance value of 0.000 < 0.05, meaning that every one unit increase in perceived value will increase revisit intention by 0.828 units. The value of R square is 0.724 indicates that perceived value has an influence on revisit intention with a percentage of 72.4%, while the remaining 27.6% is influenced by other factors.